The Effect of Customer Experience on Customer Loyalty in the Digital Era - Monica Damayanti; Mutiara Fitridiani; Raihan Pandu Prasetyo; Royan Kusniyanto; Muhammad Saeful Haddy (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:Customer experience has become a crucial factor in shaping long-term relationships between companies and customers. In increasingly competitive markets, companies must create positive experiences throughout the customer journey in order to maintain customer loyalty. This study aims to examine the effect of customer experience on customer loyalty.Methodology:The research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 100 respondents who had experienced interactions with a company’s products or services within the last six months. The sampling technique used was purposive sampling. The collected data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression analysis.Findings:The results indicate that customer experience has a positive and significant effect on customer loyalty. The regression analysis shows a positive regression coefficient (β = 0.645), indicating that better customer experience leads to higher customer loyalty. The t-test results also confirm the significance of the relationship, where the calculated t-value (6.875) is greater than the t-table value (1.984) with a significance value of 0.000.Implication:Furthermore, the coefficient of determination (R²) is 0.520, meaning that customer experience explains 52% of the variation in customer loyalty. These findings suggest that companies should focus on improving customer experience to strengthen customer loyalty and maintain long-term customer relationships.